The Use of Barium and Calcium Alloys in the Ladle Furnace Treatment of Selected Grades of Continuously Cast Steels - Derda W.; Lawenda P.; Pardela P. (Archives of Metallurgy and Materials, 2015)
The subject of the paper are the results of laboratory and industrial investigations into the use of Si - Ca - Ba alloys for modifying non-metallic inclusions. Based on laboratory tests, the morphology and chemical composition of non-metallic inclusions in carbon steel were examined before and after refining with the use of the above-mentioned alloy as a refining addition. In particular tests, variable additions of the alloy were used at a constant refining time and temperature.